Menjelajahi Dunia Tanpa Batas : Penerapan Virtual Field Trip dalam Pembelajaran Sekolah Dasar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The advancement of information and communication technology has revolutionized educational paradigms, demanding the presence of innovative and contextual learning methods. One transformative approach that is increasingly being adopted in the context of elementary education is the Virtual Field Trip (VFT) a digital-based field trip simulation that allows students to explore various educational locations virtually. This article aims to thoroughly analyze the implementation of VFT in elementary-level learning using a qualitative approach based on grounded research and life-history methods. Through observation techniques, in-depth interviews, focus group discussions, and the analysis of digital and audiovisual documents, this study reveals three main findings: (1) VFT can broaden students' horizons and sharpen their imagination by virtually bridging real learning experiences; (2) This approach enhances student engagement and enthusiasm through immersive visual and interactive presentations; and (3) Learning becomes more meaningful and contextual, as students can understand concepts directly and in an applied manner. The analysis shows that VFT is not only a pedagogical solution to physical and geographical limitations but also a strategic tool to promote critical thinking, global awareness, and cross-cultural understanding from an early age. Nevertheless, the effectiveness of VFT implementation is highly influenced by technological readiness, educators’ digital competence, as well as institutional and parental support. Therefore, a comprehensive and adaptive implementation strategy is needed to optimize the potential of VFT as an inclusive and sustainable future learning instrument in elementary schools.